Epileptogenic Zone Localization in Refractory Epilepsy by FDG-PET: The Comparison of SPM and SPM-CAT With Different Parameter Settings - Bacon, Eric Jacob; Jin, Chaoyang; He, Dianning; Hu, Shuaishuai; Wang, Lanbo; Li, Han; Qi, Shouliang (Frontiers in Neurology, 2021)
Refractory epilepsy is a complex case of epileptic disease. The quantitative analysis of Fluorodeoxyglucose positron emission tomography (FDG-PET) images complements visual assessment and helps localize the epileptogenic zone (EZ) for better curative treatment. Statistical parametric mapping (SPM) and its computational anatomy toolbox (SPM-CAT) are two commonly applied tools in neuroimaging analysis. This study compares SPM and SPM-CAT with different parameters to find the optimal approach for localizing EZ in refractory epilepsy. The current study enrolled 45 subjects, including 25 refractory epilepsy patients and 20 healthy controls. All of the 25 patients underwent surgical operations. Pathological results and the postoperative outcome evaluation by the Engel scale were likewise presented. SPM and SPM-CAT were used to assess FDG-PET images with three different uncorrected p-values and the corresponding cluster sizes (k), as in voxels in the cluster, namely p < 0.0002, k > 25; p < 0.001, k > 100; p < 0.005, k > 200. When combining three settings, SPM and SPM-CAT yielded overall positive finding score of 96.0% (24/25) and 100.0 % (25/25) respectively. However, for the individual setting, SPM-CAT achieved the diverse positive finding score of 96.0 % (24/25), 96.0 % (24/25), and 88.0 % (22/24), which is higher than that of SPM (88.0 % (22/25),76.0 % (19/25), and 72.0 % (18/25)). SPM and SPM-CAT localized EZ correctly with 28.0 % (7/25) and 64.0 % (16/25), respectively. SPM-CAT with parameter settings p < 0.0002 and k > 25 yielded a correct localization at 56.0 % (14/25), which is slightly higher than that for the other two settings (48.0 % and 20.0 %). Moderate concordance was found between the confirmed and pre-surgical EZs, identified by SPM-CAT (kappa value = 0.5). Hence, SPM-CAT is more efficient than SPM in localizing EZ for refractory epilepsy by quantitative analysis of FDG-PET images. SPM-CAT with the setting of p < 0.0002 and k > 25 might perform as an objective complementary tool to the visual assessment for EZ localization.